2019
DOI: 10.1021/acsomega.9b00129
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Epoxy Resin with Hexagonal Boron Nitride and Graphite

Abstract: Adhesion interaction of epoxy resin with the basal surfaces of h-BN and graphite is investigated with the first-principles density functional theory calculations in conjunction with the dispersion correction. The h-BN/epoxy and graphite/epoxy interfaces play an important role in producing nanocomposite materials with excellent thermal dissipation properties. The epoxy resin structure is simulated by using four kinds of fragmentary models. Their structures are optimized on the h-BN and graphite surfaces after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 73 publications
5
59
0
1
Order By: Relevance
“…The potential energy curve is plotted in 0.1 Å increments. As in many previous studies, 8 12 , 17 , 21 , 22 , 27 29 there is one inflection point in the curve. The curve was fitted using the Morse potential shown in eq 1 .…”
Section: Resultssupporting
confidence: 75%
“…The potential energy curve is plotted in 0.1 Å increments. As in many previous studies, 8 12 , 17 , 21 , 22 , 27 29 there is one inflection point in the curve. The curve was fitted using the Morse potential shown in eq 1 .…”
Section: Resultssupporting
confidence: 75%
“…Our previous study has investigated the adhesion of an epoxy fragment with the hydrophobic surface of hexagonal boron nitride: the interaction exerted at the interface is predominantly derived from dispersion forces. 25 The large contribution of dispersion energy to the adhesion of benzene investigated in the present study supports the idea that benzene rings are adsorbed on surfaces primarily through dispersion interactions. Compared to benzene adsorption, the ratios of Δ E disp to Δ E ad for the adsorption of water indicate a relatively low contribution of dispersion energy to adhesion energy.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Many experimental and theoretical studies have shown that the hydrogen bond formed by the hydroxyl group and the ether group is involved in an important interaction in the adhesion mechanism. Benzene rings can provide corrosion resistance and good thermal properties. Recent theoretical studies have shown that these rings in epoxy resins can interact with both hydrophilic and hydrophobic surfaces via OH−π interactions and π–π stacking, respectively. The epoxy group with its three-membered ring structure serves as a cross-linking site with curing agents and other materials .…”
Section: Introductionmentioning
confidence: 99%
“…5−16 Benzene rings can provide corrosion resistance and good thermal properties. Recent theoretical studies have shown that these rings in epoxy resins can interact with both hydrophilic and hydrophobic surfaces via OH−π interactions 17 and π−π stacking, 18 respectively. The epoxy group with its threemembered ring structure serves as a cross-linking site with curing agents and other materials.…”
Section: ■ Introductionmentioning
confidence: 99%